2008
DOI: 10.1291/hypres.31.525
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antihypertensive Drugs and Exercise Training on Insulin Sensitivity in Spontaneously Hypertensive Rats

Abstract: We examined the effects of antihypertensive drugs, exercise training, and combinations thereof on insulin sensitivity (IS), and the association between this relation and sympathetic activity, muscle fiber composition, and capillary density in spontaneously hypertensive rats (SHR). Six-week-old male SHR were allocated to 7 groups: a control group (C), and groups treated with azelnidipine (Aze) (a calcium channel blocker),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…22, 23 Briefly, before the start of the glucose clamp, fasting blood glucose was measured by a blood glucose test meter (A790820; GUNZE, Kyoto, Japan). An initial bolus of insulin (25 mU kg −1 of Humalin R, U-100; Eli Lilly Japan, Kobe, Japan) was infused through a venous catheter, and this step was followed by a constant infusion of insulin at a rate of 4 mU kg −1  min  for 147 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…22, 23 Briefly, before the start of the glucose clamp, fasting blood glucose was measured by a blood glucose test meter (A790820; GUNZE, Kyoto, Japan). An initial bolus of insulin (25 mU kg −1 of Humalin R, U-100; Eli Lilly Japan, Kobe, Japan) was infused through a venous catheter, and this step was followed by a constant infusion of insulin at a rate of 4 mU kg −1  min  for 147 min.…”
Section: Methodsmentioning
confidence: 99%
“…The average rate of glucose infusion (mg kg −1  min −1 ) for the last 35 min was taken as an index of IS (M value). 22, 23 …”
Section: Methodsmentioning
confidence: 99%
“…Ten microliters of arterial blood were sampled through an arterial catheter at 7-min intervals for determination of the blood glucose. The average of the rate of glucose infusion (mg/kg per min) for the last 35 min was taken as an index of insulin sensitivity (M value) [13].…”
Section: Euglycemic Hyperinsulinemic Glucose Clamp Techniquementioning
confidence: 99%
“…Although no alteration in the composition of types of fiber was observed in the trained SHR and SHR treated with perindopril groups when compared with the sedentary SHR group, the authors observed higher capillarization in these groups, which may be attributed to improvement in the exercise capacity. A more recently study from the same group showed that pharmacological treatment with a calcium channel blocker (azelnidipine), or an antagonizer of type I angiotensin receptor (olmesartan) or even the ET significantly increased capillary density and percentage of type I fibers in the soleus muscle of SHR 32 . Although the results in the literature are still controversial concerning the alterations in proportion of the types of fiber in response to ET, it was not possible either to observe the comparison between the profile of the types of fiber in the trained SHR group compared with its normotensive control WKY, with the aim to check normalization with the fiber type composition.…”
Section: Discussionmentioning
confidence: 98%